Micro-pocket fission detectors: development of advanced, real-time in-core, neutron-flux sensors - Reichenberger, Michael Anthony (Kansas State University, 2017)
Advancements in nuclear reactor core modeling and computational capability have encouraged further development of in-core neutron sensors. Measurement of the neutron-flux distribution within the reactor core provides a more complete understanding of the operating conditions in the reactor than typical ex-core sensors. Micro-Pocket Fission Detectors (MPFDs) have been developed and tested previously but have been limited to single-node operation and have utilized highly specialized designs. The development of a widely deployable, multi-node MPFD assembly will enhance nuclear research capabilities. In-core neutron flux measurements include many challenges because of the harsh environment within the reactor core. Common methods of in-core neutron measurement are also limited by geometry and other physical constraints. MPFDs are designed to be small and robust while offering a real-time, spatial measurement of neutron flux. Improvements to the MPFD design were developed based on shortcomings of prior research in which many of the theoretical considerations for MPFDs were examined. Fabrication techniques were developed for the preparation of MPFD components and electrodeposition of fissile material. Numerous arrays of MPFDs were constructed for test deployments at the Kansas State University TRIGA Mk. II research nuclear reactor, University of Wisconsin Nuclear Reactor, Transient REActor Test facility at the Idaho National Laboratory (INL), and Advanced Test Reactor at INL. Preliminary testing of a single MPFD sensor at KSU yielded a linear response to reactor power between 10 kWth and 750 kWth and followed both positive and negative reactivity insertions in real-time. A $1.50 reactor pulse was monitored from the Intra-Reflector Irradiation System, located in reflector region of the KSU TRIGA Mk. II core with 1-ms time resolution. Improved multi-node MPFD arrays were then designed, fabricated, and deployed in flux ports between fuel rods and within an iron-wire flux port which was inserted into the central thimble of the KSU TRIGA Mk. II research nuclear reactor. Work continues to develop MPFDs for deployment at research reactors at INL and elsewhere. Results from the MPFD measurements will be useful for future validation of computational modeling and as part of advanced nuclear fuel development efforts.
Keywords: MPFD; In-core instrumentation; Nuclear instrumentation; Fission chamber; TREAT